AR-RAHNU AS A SOURCE OF FINANCIAL SUSTAINABILITY FOR WOMEN MICRO-ENTREPRENEURS IN MALAYSIA - Nik Azman, Nik Hadiyan; Hj. Kassim, Salina (Journal of Islamic Monetary Economics and Finance, 2017)
Muslims in Malaysia had practiced ar-rahnu for fulfilling their financial need, especially for emergency purposes since early 1990s. The pioneer of ar-rahnu in Malaysia is Muassasah Gadaian Islam Terengganu (MGIT) in January 1992, followed by the Kelantan Capitalization Berhad (PKB) in March 1992. Both of these Islamic pawn centres are among the earliest exponents to the Islamic pawn scheme in Malaysia. Ar-rahnu is an increasingly popular financing option among micro-entrepreneurs in Malaysia, particularly women micro-entrepreneurs. Women micro-entrepreneurs play a vital role in the Malaysian economy and could be considered as the backbone of the industrial development in Malaysia. This study examines the role of ar-rahnu as a source of financial stability for women micro-entrepreneurs. 600 questionnaires were distributed at three states in Malaysia which are Kelantan, Terengganu and Kedah. Then, this study used SPSS and SEM Amos to analyses the data for 600 respondents (women micro-entrepreneurs) in Malaysia. In essence, this study finds that shariah compliancy, locality, service charges, collateral and customer satisfaction has positive and significant impact towards the use of ar-rahnu. The study also found use of ar-rahnu has significant impact towards financial self-sufficiency for women micro-entrepreneurs.